(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Day care surgery is widely acceptable and gaining popularity for more than a decade. Early recovery and cost effectiveness is an integral part of day care surgery in developing country. Objective To compare the cost effectiveness & recovery score after oral midazolam and thiopental sodium or propofol induction in day care surgery. Methods A total number of sixty patients, thirty in each group of ASA grade I & II were selected. In group -A patient receiving propofol 2mg/kg for induction and group B were given oral midazolam 0.25mg/ kg thirty minutes before induction with thiopental sodium 2.5mg/kg. Perioperative heart rate, BP, recovery score and time to ready to go home were monitored. Average cost of induction was calculated in both groups. Result Recovery scores in group A & B were 8.8 ±1.75 and 8.01 ±1.03 respectively after thirty minutes of reversal. The cost of group B (BDT 37.88±1.37) was significantly lower (P<0.05) than that of group A (BDT 142.00 ± 6.00). Conclusion Preoperative oral midazolam & low dose thiopental sodium induction is relatively cost effective than propofol induction in day care surgery. JBSA 2012; 25(1): 9-13